Laminar Differences in the Targeting of Dendritic Spines by Cortical Pyramidal Neurons and Interneurons in Human Dorsolateral Prefrontal Cortex. (1st January 2021) - Glausier, Jill R.; Datta, Dibyadeep; Fish, Kenneth N.; Chung, Daniel W.; Melchitzky, Darlene S.; Lewis, David A.
Highlights: In human DLPFC more spines innervated by pyramidal cells in middle than deep layers. Spines dually innervated by pyramidal cells and interneurons present in both layers. More dually innervated spines in middle than deep layers of human DLPFC. These spine types may contribute to laminar-specific functions of DLPFC. Abstract: Activation of specific neural circuits in different layers of the primate dorsolateral prefrontal cortex (DLPFC) is essential for working memory, a core cognitive function. Recurrent excitation between pyramidal neurons in middle and deep layers of the DLPFC contributes to the laminar-specific activity associated with different working memory subprocesses. Excitation between cortical pyramidal neurons is mediated by glutamatergic synapses on dendritic spines, but whether the relative abundance of spines receiving cortical inputs differs between middle and deep cortical layers in human DLPFC is unknown. Additionally, GABAergic inputs to spines sculpt pyramidal neuron activity. Whether dendritic spines that receive a glutamatergic input from a cortical pyramidal neuron are targeted by GABAergic interneurons in the human DLPFC is unknown. Using triple-label fluorescence confocal microscopy, we found that 1) the density of spines receiving an input from a cortical pyramidal neuron is greater in the middle than in the deep laminar zone, 2) dendritic spines dually innervated by a cortical pyramidal neuron and an interneuron are present in the human DLPFC, and 3) the density of spines dually innervated by a cortical pyramidal neuron and an interneuron is also greater in the middle than in the deep laminar zone. Ultrastructural analyses support the presence of spines that receive a cortical pyramidal neuron synapse and an interneuron synapse in human and monkey DLPFC. These data support the notion that the DLPFC middle laminar zone is particularly endowed with a microcircuit structure that supports the gating, integrating and fine-tuning of synaptic information in recurrent excitatory microcircuits.